Philosophy with children and education for human rights : including workshop examples - Ćurko, Bruno (Array, 2021)
Philosophy with children officially begins with Matthew Lipman who initiated it in the 1970s. He was prompted to do so by the fact that his students struggled with critical thinking. This encouraged him to establish the Institute for the Advancement of Philosophy for Children at Montclair State University. Even though the movement has faced some criticism, it continues to spread around the world. The reason for this are the methods used, i.e. stories, games, conversations, questions, etc., as well as the topics analysed. Philosophy with children addresses numerous topics, while this paper will focus on human rights, more specifically, what human rights are, what the most important human rights are, and how they might be violated. In order to make this subject matter more accessible to children, at the end of the paper, an overview of two workshops is given, which may be applied to the subject of human rights in practicing philosophy with children.